Lack of Cryptococcus gattii from Eucalyptus in Ahvaz - Zahra Salehei; Ali Zarei Mahmoudabadi; Majid Zarrin (Mazandaran University of Medical Sciences, 2015)
The basidiomycetous yeast genus Cryptococcus contains two medically important pathogens, Cryptococcus neoformans and C. gattii [1-3]. C. neoformans is one of the common pathogens in acquired immunodeficiency syndrome (AIDS), whereas the most cases of diseases due to C. gattii happened in the healthy individuals [2, 4]. C. gattii has a tendency to affect the respiratory and nervous systems of the humans and domestic animals such as, dogs, cats, and horses [5]. C. gattii is more geographically restricted than C. neoformans and is largely confined to tropical and subtropical regions. Several reports show that C. gattii was isolated from Eucalyptus trees (Eucalyptus tereticornis, E. citriodora and E. camaldulensis) in Australia [4, 6, 7].